Blastic plasmacytoid dendritic cell neoplasm: First retrospective study in the Czech Republic - Cernan, M; Szotkowski, T; Hisemová, Miloslava; Cetkovsky, P; Sramkova, L; Stary, J; Racil, Z; Mayer, J; Sramek, J; Jindra, P; Visek, B; Zak, P; et al. (Neoplasma, 2020)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare hematologic malignancy with aggressive behavior and poor prognosis. We present the first retrospective analysis mapping its incidence and therapeutic outcomes in patients diagnosed and treated from 2000 to 2017 in the Czech Republic. The cohort comprised 14 patients (10 males, 4 females) with a median age at diagnosis of 39 years (range, 5-68 years). Initially, skin involvement was noted in 10 (71%) patients and bone marrow infiltration was present in 9 (64%). The first complete remission was achieved in 6/14 (43%) patients after acute lymphoblastic leukemia/lymphoma induction therapy and in 3/14 (21%) patients after acute myeloid leukemia regimen. Nine patients underwent allogeneic hematopoietic cell transplantation, with two patients achieving the first complete remission only after allogeneic transplantation. Patients undergoing allogeneic hematopoietic cell transplantation had longer overall survival than those treated without transplantation (the median survival over the period 16.4 vs. 8.1 months). Relapse of the disease was a significant predictor of mortality (p=0.05). Over the study period, patients' survival ranged from 3.3 to 44.2 months, with a median overall survival of 13 months. Our results revealed an effectivity of allogeneic hematopoietic cell transplantation on complete remission achievement in refractory/relapsed disease. The study aimed to present the actual data from the Czech Republic and thus contribute to a global understanding of BPDCN.
Keywords: Adolescent; senioři; Male; Female; mladý dospělý; dítě; Aged; Middle Aged; Young Adult; dendritické buňky; Česká republika; recidiva; hematologické nádory; Dendritic Cells; transplantace hematopoetických kmenových buněk; předškolní dítě; mužské pohlaví; indukce remise; ženské pohlaví; Adult; Czech Republic; Hematopoietic Stem Cell Transplantation; Child; Recurrence; Retrospective Studies; mladiství; retrospektivní studie; dospělí; lidé středního věku; lidé; Humans; Remission Induction; Hematologic Neoplasms; Child, Preschool